A new model of how celebrity endorsements work: attitude toward the endorsement as a mediator of celebrity source and endorsement effects. Issue 2 (3rd March 2016) - Bergkvist, Lars; Hjalmarson, Hanna; Mägi, Anne W.
Abstract : This research introduces attitude towards the endorsement as a mediating variable in the relationships between celebrity source and endorsement factors and brand attitude. It also includes perceived celebrity motive, a variable rarely studied in the previous literature, as an endorsement factor. In a survey study, respondents evaluated four celebrity endorsement campaigns. Mediation analyses show that attitude towards the endorsement mediates the effects of three variables on brand attitude; these variables are celebrity expertise, celebrity–brand fit, and perceived celebrity motive. Moreover, results show that if consumers perceive that the celebrity was motivated to do the endorsement not only by money but also by product quality, this has a significant positive effect on attitude towards the brand.